Cognitive impairment and whole brain diffusion in patients with carotid artery disease and ipsilateral transient ischemic attack. (January 2014) - Guo, Jian; Wang, Shanshan; Li, Rong; Chen, Ning; Zhou, Muke; Chen, Huafu; Gong, Qiyong; He, Li
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Transient ischemic attack (TIA) with carotid artery disease (CAD) can increase the risk of cognitive decline. However, the neural mechanisms of the disorder remain unclear. The aim of this study was, using diffusion tensor imaging (DTI), to detect microstructural changes in patients with symptomatic CAD presenting with TIA, and to explore their relationship with cognitive functions. Methods: In all, 35 patients with right-sided CAD and ipsilateral TIA and 35 healthy controls were investigated using cognitive tests and voxel-based analysis (VBA) of DTI. The whole brain DTI parameters, fractional anisotropy (FA) and mean diffusivity (MD), were calculate and compared between two groups. A correlation analysis was also performed to explore the relationship between cognitive test scores and whole brain FA and MD values in the patients. Results: We observed two interesting findings. First, compared with the controls, the patients showed significantly increased MD in the right anterior cingulate gyrus (ACG) and decreased FA in the right amygdala. Second, the MD values in the right ACG were negatively correlated with Montreal Cognitive Assessment (MoCA) in the patients. Conclusions: Diffusion tensor imaging parameters are altered in patients with CAD and ipsilateral TIA, which indicates the existence of microstructural abnormalities in the brain of the patients. The significant correlation between DTI abnormalities and cognition reveals the potential of DTI for investigating the pathophysiology mechanism related to the cognitive dysfunction of the disease.